Fostering Harmony Amidst Diversity: Religious Moderation and its Role in the Social-Political Contexts of Malaysia - Nabila Tussa'bannniya; Puspa Arum Yasinatul (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2025)
This article specifically examines the dynamics and challenges of Islamic moderatism in Malaysia in the socio-political landscape. This is an important issue to be explored further, because lately moderation and radicalization in Islamic discourse have not only affected political stability but also social conditions in plural Malaysia. The writing of this article uses qualitative methods in the process of data collection and analysis. By using a deductive approach by understanding the arguments and opinions of academics and credible and academically tested literature sources, it becomes the main reference in the preparation of this paper. The result is that the Malaysian government promotes moderate Islam through state initiatives in instilling moderate Islamic values such as (Islam hadhari, wasatiyah, and rahmatan-lil-‘alamin). The societal response to radicalism and liberalism in Malaysia involves various government and NGO initiatives, including public education, talk shows, publications and seminars. These efforts aim to monitor and reduce the influence of liberal Islam, which is perceived as a threat. The existence of social media as a stream of technological development also plays an important role in shaping moderate Islamic discourse in Malaysia, serving as a platform for the dissemination of moderate views and countering extremist narratives. The involvement of other elements such as the role of Islamic parties in shaping moderate policies in Malaysia is significant in understanding and adapting to Malaysia's complex political dynamics. They strive to balance Islamic principles with democratic values, thus promoting a more moderate political discourse.